Retinal nerve fiber layer thickness and rim area profiles in Asians: pooled analysis from the Asian Eye Epidemiology Consortium - Majithia, Shivani; Tham, Yih-Chung; Chong, Crystal Chun Yuen; Yu, Marco; Cheung, Carol Y.; Bikbov, Mukharram M.; Kazakbaeva, Gyulli M.; Wang, Ningli; Hao, Jie; Cao, Kai; Wang, Ya Xing; Sasaki, Mariko; et al. (Ophthalmology, 2022)
Purpose - To evaluate ethnic variations, ocular and systemic determinants of retinal nerve fiber layer (RNFL) thickness, and neuroretinal rim area among Asians using a large consortium of population-based eye studies. - Design - Cross-sectional pooled analysis. - Participants - Twenty-two thousand four hundred thirty-six participants (22 436 eyes) from 10 population-based studies (in China, Hong Kong, India, Japan, Russia, and Singapore) of the Asian Eye Epidemiology Consortium. - Methods - Participants 40 years of age or older without glaucoma were included. All participants underwent spectral-domain OCT imaging and systemic and ocular examinations. Data were pooled from each study. Multivariable regression was performed to evaluate interethnic differences, intermachine variations, and ocular and systemic factors associated with RNFL thickness and rim area, adjusting for age, gender, diabetes, intraocular pressure (IOP), spherical equivalent (SE), ethnicity, OCT model, and study group. When evaluating body mass index, smoking, and hypertension as exposures, these factors were additionally adjusted for in the model. - Main Outcome Measures - Average RNFL thickness (in micrometers) and rim area (in square millimeters). - Results - Indian and Japanese eyes have thinner RNFLs than those of other Asian ethnicities (β values range, 7.31-12.76 μm; P < 0.001 for all pairwise comparisons). Compared with measurements by Cirrus HD-OCT (Carl Zeiss Meditec, Inc), RNFL on average was 7.29 μm thicker when measured by Spectralis (Heidelberg Engineering), 12.85 μm thicker when measured by RS-3000 (NIDEK Co, Ltd), and 17.48 μm thicker when measured by iVue/RTVue (Optovue, Inc) devices (all P < 0.001). Additionally, older age (per decade, β = -2.70), diabetes (β = -0.72), higher IOP (per 1 mmHg, β = -0.07), more myopic SE (per diopter, β = -1.13), cardiovascular disease (β = -0.94), and hypertension (β = -0.68) were associated with thinner RNFL (all P ≤ 0.003). Similarly, older age (β = -0.019), higher IOP (β = -0.010), and more myopic SE (β = -0.025) were associated with smaller rim area (all P < 0.001). - Conclusions - In this large pooled analysis of Asian population studies, Indian and Japanese eyes were observed to have thinner RNFL profiles. These findings suggest the need for an ethnic-specific normative database to improve glaucoma detection.